KONSEP TIJAROH SEBAGAI SOLUSI FENOMENA PERDAGANGAN DENGAN SISTEM TEBAS TERHADAP KOMODITAS PADI DAN MANGGA DI KABUPATEN NGAWI - Hanafi, Yusron (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
The total area of Ngawi Regency is 1,298.58 km2, of which 506.6 km2 or about 40% is made up of rice fields. According to the data, farmers employ the bulk of Ngawi people. Mango fruit is the second most abundant good after rice, as most Ngawi people grow mango trees in front or behind their homes. When harvest season rolls around, farmers have trouble finding buyers who will purchase their crops in an honest and profitable manner. This is because buyers, also known as penebas, use the Tebas system to complete the purchase process for these two commodities, which means that the system cannot fulfill the wishes of both parties involved in the transaction if It also goes by the name "profit" in economics.According to the Tijaroh principle, the goal of a trading contract is to find and make money when all requirements have been met. Ijarah, Salam, Murabahah, Istishna', Musyarakah, Muzara'ah, and Mukharabah, musaqah are among the contracts that fall under this category. Or, according to a different editorial, any kind of arrangement involving for-profit transactions is referred to as a tijarah contract (compensational contract).The goal of this research is to stop Maysir and Gharar practices in the trade of rice and mango commodities in the Ngawi district and to make rice trading activities ethical and advantageous for all stakeholders.Issue. The present study employed the Inductive analysis method in a Normative approach to examine the data. This entails evaluating the research object's problems beforehand and utilizing the Tijaroh concept to analyze the data. Keywords: Tebas, Trade, and Tijaroh